Relevance of Biomarkers Currently in Use or Research for Practical Diagnosis Approach of Neonatal Early-Onset Sepsis - Maura-Adelina Hincu; Gabriela-Ildiko Zonda; Gabriela Dumitrita Stanciu; Dragos Nemescu; Luminita Paduraru (MDPI AG, 2020)
Neonatal early-onset sepsis (EOS) is defined as an invasive infection that occurs in the first 72 h of life. The incidence of EOS varies from 0.5-2% live births in developed countries, up to 9.8% live births in low resource settings, generating a high mortality rate, especially in extremely low birth weight neonates. Clinical signs are nonspecific, leading to a late diagnosis and high mortality. Currently, there are several markers used for sepsis evaluation, such as hematological indices, acute phase reactants, cytokines, which by themselves do not show acceptable sensitivity and specificity for the diagnosis of EOS in neonates. Newer and more selective markers have surfaced recently, such as presepsin and endocan, but they are currently only in the experimental research stages. This comprehensive review article is based on the role of biomarkers currently in use or in the research phase from a basic, translational, and clinical viewpoint that helps us to improve the quality of neonatal early-onset sepsis diagnosis and management.